Integrating technology pedagogy and content knowledge in Qatar’s preparatory and secondary schools: The perceptions and practices of STEM teachers - Ziad Said (17541819) (2023)
This paper is part of a project on enhancing STEM teaching through teachers’ professional development (TPD). The aim is to explore K-12 science and mathematics teachers’ views and practices about implementing STEM through technological pedagogical content knowledge (TPACK) model in Qatar and identify their challenges. The objective is to develop a TPD program using project-based learning pedagogical intervention to support K-12 science and mathematics teachers and to train them on how to implement PBL in their teaching practices. 245 STEM teachers from 16 preparatory and secondary schools, representing an equal number of males and females, responded to a STEM-TPACK survey on perceptions of and practices in teaching STEM subjects. One hundred thirty-seven preparatory (grades 7-9) and 108 secondary school teachers (grades10-11). Generally, there are no significant differences between the different dual groups in understanding STEM, TPACK, and embedding technology, with few exceptions in some aspects. This reflects a high consistency in teaching, pedagogy, and learning environments among these groups (gender, teaching level, and STEM subjects taught). Preparatory school teachers show more variations in all elements of TPACK than secondary school teachers, as reflected by values of standard errors of the mean (SEM). Male teachers show slightly more understanding of elements of TPACK and have somewhat higher means than female teachers. SEM for female teachers is slightly higher, indicating more variation among female teachers than male teachers. However, the difference is also insignificant, as characterized by the small effect sizes ranging from 0.13 to 0.31, small t-test values, and high p-values. Other Information Published in: Eurasia Journal of Mathematics, Science and Technology Education License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.29333/ejmste/13188